The impact of positive activities on mental health: the mediating role of positive emotion - Wang, Yanting; Wu, Yuanyang; Xu, Qianqian; Fan, Si; Hu, Jinwen; Zou, Dongdong; Zhang, Xinping (Frontiers in Public Health, 2024)
ObjectiveMental health has become a widely concerned topic worldwide. However, the impact and mechanism of positive activities on mental health still needed to be explored. This study aimed to apply the positive-activity model to investigate the effect of participation in positive activities on mental health and the mediating role of positive emotion.MethodsThis study used data from the 2021 China Comprehensive Social Survey (CGSS) and included 2,581 individuals. Ordinary Least Squares (OLS) and a three-step method was used for analysis.ResultsThe average of positive activities was 15.83. The positive activities affected positively mental health (β = 0.0132, p < 0.001). The positive emotion played a mediating role (β =0.2281, p < 0.001). The effect of positive activities on mental health was significant in older adults group (β = 0.024, p < 0.001), female (β = 0.015, p < 0.01) and male group (β = 0.01, p < 0.01), unmarried/divorced/widowed group (β = 0.024, p < 0.01), cohabitation/first marriage with spouse/remarriage with spouse/separation without divorce group (β = 0.010, p < 0.001), middle(β = 0.013, p < 0.05), and upper-middle-level SES group (β = 0.054, p < 0.001).ConclusionsWe concluded that the participation level of positive activities still needs to be improved and positive activities improve mental health through positive emotion, which implied that positive activities, as an easily implementable measure, should be greatly encouraged in mental health policies. And older adults, female, people without spouse, middle and upper-middle-income individuals need to be paid more attention.